Mechanisms of drug interactions: pharmacodynamics and pharmacokinetics. Issue 7 (July 2017) - Corrie, Kathryn; Hardman, Jonathan G.
Abstract: The classification of drug interactions is first considered in this article, with an explanation of the terminology. Emphasis is placed on the importance of the topic in relation to the polypharmacy employed in anaesthesia and critical care. Pharmacodynamic interactions are then discussed. Further classification of these interactions is explained using examples of drugs in everyday use in anaesthesia and critical care medicine. Non-specific pharmacodynamic interactions are considered at some length, being the largest group of drug interactions that occur in anaesthesia. Synergy and summation are extremely relevant to anaesthetic practice and are employed in both induction and maintenance of anaesthesia everyday. The article then explains pharmacokinetic interactions under the headings of absorption, distribution, metabolism and elimination. Again, emphasis is placed on drugs used in current practice to highlight the relevance of each type of interaction to the reader.